Criticism of Margin Actualization in Murābahah Financing at Sharia Banking Evidence from Indonesia - Reni Furwanti; Dini Maulana Lestari; Abdul Mustaqim; Iin Solikhin (Postgraduate Program, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This study aims to analyze margin actualization of murābaha contract. It is because, although murābaha is a favorable financing contract at sharia banking, it still has problem due to the related issue. This happens due to lack of trust form such customers, who have a tendency that sharia bank is the same with conventional bank due to the issue of margin actualization. This is a qualitative descriptive reseach with library reseach approach, exploring the issue and relating to the Islamic study to get such deep analysis. The result revealed that relating to the issue it needs such a fatwa or other binding which aligned with sharia principles, and such reconstruction of the contract which appropriate with sharia principle reflected by maqāṣid al-sharia.